(3GdJMcje GdJLGQj GdOhdjIs (3OQGSI ebGQfI dCMcGe GdJMcje GdJLGQj GdOhdj ceG LGAJ aj GdbhGYO hGdGJaGbjGJ GdOhdjI hGdGbdjejI hGdYdGHjI eY ETGQI Edi CMcGe GdJMcje aj GdJTQjYGJ GdYQHjIs - (3SGej(B, (3ahRj eMeOs ((3YeGfs (3OGQ GdKbGaI ddfTQ h GdJhRjYs, 2006)
(3aj gPG GdcJGH OQGSI ebGQfI dCMcGe GdJMcje GdJLGQj GdOhdj ceG LGAJ aj GdbhGYO hGdGJaGbjGJ GdOhdjI hGdEbdjejI hGdYQHjI eY ETGQI Edi CMcGe GdJMcje aj GdJTQjYGJ GdYQHjI, aj GdHOGjI YQaJ GdOQGSI HCgejI GdJMcje ef NdGd GdGJaGbjGJ GdOhdjI hGdEbdjejI GdYQHjI hGdCLfHjI GdJj YbOJ aj gPG GdeLGd, Ke OQSJ CMcGe GdJMcje efP GJaGb GdWQajf GdeJYGbOjf Ydi GJHGYg dMSGe NdGaGJge, dMjf EUOGQ GdbQGQ GdJMcjej hJfajPg Ch GdWYf ajg, hde JbJUQ Ydi CMcGe GdJMcje GdJLGQj GdOhdj, Hd TedJ GdJMcje HhLg YGe, hPdc dCf GdJMcje GdOhdj bO jNVY dCMcGe GdbGfhf GdeMdj ShGA CcGf Pdc HGdfSHI ddELQGAGJ Ch HGdfSHI ddbGfhf GdPj jWHb Ydi ehVhY GdfRGY(B. (3ceG Cf JfajP GdbQGQ GdJMcjej jNVY aj GdZGdH ddbhGYO GdELQGFjI dbGfhf GdHdO GdeQGO JfajP GdbQGQ ajg ebOeI (B: (3GdHGH GdJegjOj (B: (3GdaUd GdChd (B: (3JYQja GdJMcje (B: (3GdaUd GdKGfj (B: (3eRGjG GdJMcje (B: (3GdaUd GdKGdK (B: (3Cge GdeDSSGJ GdJMcjejI aj GdYGde(B-(3GdHGH GdChd (B: (3GdaUd GdChd (B: (3GdGgJeGe HGdJMcje aj fWGb GdJLGQI GdOhdjI (B: (3GdaUd GdKGfj (B: (3GdGJaGbjGJ GdEbdjejI (B: (3GdaUd GdKGdK (B: (3eJi jYJHQ GdJMcje OhdjG ?(B-(3GdHGH GdKGfj (B: (3GdaUd GdChd (B: (3GJaGb GdJMcje (B: (3GdaUd GdKGfj (B: (3GNJjGQ GdeMcejf (B: (3GdaUd GdKGdK (B: (3bGfhf GdJMcje (B: (3GdaUd GdQGHY (B: (3GdbGfhf GdhGLH GdJWHjb Ydi ehVhY GdfRGY (B: (3GdaUd GdNGeS (B: (3GSJbdGdjI TQW GdJMcje (B: (3GdaUd GdSGOS (B: (3YbO GdJMcje(B-(3GdHGH GdKGdK (B: (3GdaUd GdChd (B: (3GdSjQ aj ELQGAGJ GdJMcje (B: (3GdaUd GdKGfj (B: (3GUOGQ GdbQGQ GdJMcjej heMJhjGJg (B: (3GdaUd GdKGdK (B: (3GKGQ GdbQGQ GdJMcjej (B: (3GdaUd GdQGHY (B: (3JfajP GdbQGQ GdJMcjej (B: (3GdaUd GdNGeS (B: (3GdWYf aj GdbQGQ GdJMcjej(B-(3GdHGH GdQGHY (B: (3GdaUd GdChd (B: (3ehba GdOhd GdYQHjI ef GdJMcje GdJLGQj GdOhdj (B: (3GdaUd GdKGfj (B: (3ehba GdYQGb ef GdJMcje GdJLGQj GdOhdj(B.s
Keywords: (3GdJLGQI GdOhdjIs; (3GdbGfhf GdOhdjs